Micromachined Acoustic Transducers for Audio-Frequency Range (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
Microelectromechanical systems (MEMSs) and acoustics have become inseparable disciplines. MEMS microphones have become one of the most successful commercial products in the history of microsystem technology. In recent years, MEMS speakers have garnered significant interest from both research and industry. This Special Issue is dedicated to showcasing works on micromachined acoustic transducers for the audio-frequency range and providing a state-of-the-art overview of this dynamic field as it pertains to audio applications.The articles in this Special Issue cover a range of topics within the domain of MEMS acoustic devices, including microphones, speakers, and hearing aids. They address key research questions related to the design, modeling, evaluation, and applications of these devices. The diverse origins of the contributing authors—from industry, academia, and research institutions—bring a multidisciplinary perspective that ensures a comprehensive and balanced exploration of the field. This diversity also guarantees the practical relevance and scientific rigor of the presented works, offering valuable insights for researchers and engineers alike.